A brief review on fatigue test of ceramic and some related matters in Dentistry. (February 2023) - Valandro, Luiz Felipe; Cadore-Rodrigues, Ana Carolina; Dapieve, Kiara Serafini; Machry, Renan Vaz; Pereira, Gabriel Kalil Rocha
Abstract: The characteristics of dental ceramics have been extensively studied over the years to provide highly qualified materials for use in prosthetic restorations. The ability to adhere to dental substrates, outstanding aesthetics (translucency, color, and substrate masking ability) and improved mechanical properties provide these materials with optical features and high strength to withstand masticatory stimuli. Different classifications are adopted, and it is generally considered that glass-ceramics have better optical characteristics due to the high glass content, and polycrystalline ceramics have superior strength favored by their densified and organized crystals, hampering crack growth. This knowledge was largely built-up during years of scientific research through different testing methodologies, but mainly employing static loads. It is important to not only take into account the intensity of loads that these materials will be exposed to, but also the effect of the intermittence of cyclic load application leading to mechanical fatigue and the influence of factors related to the crack origin and their propagation under this condition. Furthermore, the bonding surface of ceramic restorations requires surface treatments that improve the bond strength to luting agents; however, these treatments require caution because of their potential to produce defects and affect the structural behavior. Moreover, ceramic restorations often require internal adjustments for proper seating or external adjustments for fitting the occlusal contact with the antagonist. In this sense, finishing/polishing protocols may alter the defect population, as luting agents may also interact by filling in the superficial defects on the restoration intaglio surface. Thus, the balance among all these factors will define the performance of a restorative setup, as well as the posterior exposure to the humid environment and the masticatory stimuli (cyclical loading), which may favor developing slow and subcritical growth of cracks in ceramic materials and the degradation of the bond interface. Therefore, it is essential that the concepts which explain the fatigue mechanism are understood, as well as the crack propagation and failure patterns of restorative ceramic materials. Highlights: Fatigue testing to inspect the mechanical behavior of dental ceramics. Intermittent cyclical loading is important to induce mechanical fatigue of ceramics. Several factors influence the mechanical behavior under the fatigue of ceramic materials. Balance among surface treatment, adhesion, and flaw population is a predictor of the mechanical fatigue behavior of ceramics.